2019
DOI: 10.1101/747014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma membrane damage causes NLRP3 activation and pyroptosis during Mycobacterium tuberculosis infection

Abstract: AbstractMycobacterium tuberculosis (Mtb) is a major global health problem and causes extensive cytotoxicity in patient cells and tissues. Here we define an NLRP3, caspase-1 and gasdermin D-mediated pathway to pyroptosis in human monocytes following exposure to Mtb. We demonstrate an ESX-1 mediated, contact-induced plasma membrane (PM) damage response that occurs during phagocytosis or from the cytosolic side of the PM after phagosomal rupture in Mtb i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…20,30 We therefore investigated if Mav or MavCs are phagosomal rupture and plasma membrane damage. 29 As expected, Galectin-3 recruitment and ubiquitination was associated with auxo-TB-BFP 24 h post infection (Fig. 3C and D).…”
Section: Antibiotic Treatment Does Not Target Mav or Mavcs For Autophagysupporting
confidence: 81%
See 1 more Smart Citation
“…20,30 We therefore investigated if Mav or MavCs are phagosomal rupture and plasma membrane damage. 29 As expected, Galectin-3 recruitment and ubiquitination was associated with auxo-TB-BFP 24 h post infection (Fig. 3C and D).…”
Section: Antibiotic Treatment Does Not Target Mav or Mavcs For Autophagysupporting
confidence: 81%
“…We and others have shown that Mtb is able to destabilize the phagosomal membrane and establish contact with the cytosol. [26][27][28][29] However, no such ability has been shown for Mav, likely because Mav lacks the type VII secretion system ESX-1 thought to mediate the membrane perturbations by Mtb. 26 Galectins are cytosolic proteins that bind to galactosides on the luminal side of endomembranes.…”
Section: Antibiotic Treatment Does Not Target Mav or Mavcs For Autophagymentioning
confidence: 99%
“…Still elusive, these mechanisms may need more study. Mtb-induced excessive pyroptosis also aids in the spread of Mtb (Beckwith et al, 2020;Fu et al, 2021;Li et al, 2022). This process relies on the NLRP3/ caspase-1/ GSDMD axis connected with the potassium efflux, but also strongly on the ERS induction linked with TXNIP downstream upregulation and the PERK/eIF2/CHOP axis (Gong et al, 2019;FIGURE 2 Manipulation of macrophage intracellular processes by Mtb.…”
Section: Pyroptosismentioning
confidence: 99%
“…Section 5 provides more details. Beckwith et al, 2020;Li et al, 2022). Inhibiting pyroptosis in Mtbinfected macrophages through the PERK/eIF2/TXNIP/NLRP3/ caspase-1/GSDMD axis reduces lung tissue damage and Mtb dissemination (Fu et al, 2021;Li et al, 2022).…”
Section: Pyroptosismentioning
confidence: 99%
“…Several studies have mechanistically shown how distinct flavors of necrosis (e.g. inflammasome-mediated pyroptosis, RIPK-dependent necroptosis, ferroptosis) promote Mtb pathogenesis (17)(18)(19)(20)(21). We and others have begun to link cell death during Mtb infection with disruptions in mitochondrial homeostasis (14,(22)(23).…”
Section: Introductionmentioning
confidence: 99%